Whole body mechanics differ among running and cutting maneuvers in skilled athletes - Havens, K. L.; Sigward, S. M. (Gait and Posture, 2015)
Quick changes of direction during running (cutting) represent a whole body mechanical challenge, as they require deceleration and translation of the body during ongoing movement. While much is known with respect to whole body demands during walking turns, whole body mechanics and anticipatory adjustments necessary for cutting are unclear. As the ability to rapidly change direction is critical to athletes` success in many sports, a better understanding of whole body adjustments made during cuts is needed. Whole body center of mass velocity and position during the approach and execution steps of three tasks (straight running, 45° sidestep cut, and 90° sidestep cut) performed as fast as possible were compared in 25 healthy soccer athletes. Repeated measure ANOVA revealed that overall, braking and translation were greater during the cuts compared to the straight run. Interestingly, with systematically increased cut angle, disproportionately greater braking but proportionately greater translation was observed. Anticipatory adjustments made prior to the execution of the cuts suggested that individuals evenly distributed the deceleration and redirection demands across steps of the 45° cut but prioritized deceleration over translation during the approach step of the 90° cut.